Factors influence spontaneous buying behavior toward perfume product / Hanis Nor Mohamed Zailani and Muhamad Ziqrul Haqeem Shahran - Nor Mohamed Zailani, Hanis; Shahran, Muhamad Ziqrul Haqeem (Faculty of Business and Management, 2014)
The aim of this study is to determine the factors that influence customer when they want to buy perfume product. Perfume is like other personal grooming and beauty items, the purchase decision for perfume also complex one comprising of such factors like the product, price, place and also promotion. The outcomes have confirmed that customer is willing to spend their share of wallet if fragrances of high quality are offered with attractive packaging and beautifully design perfume bottles. It will attract customer to buy, repeat purchase and the product will be recommended as well.